Comparative study of hybrid cryptographic solutions (classical + post-quantum) for maintaining performance and security in IaaS in the face of quantum threats in a transitional period towards fully PQC1 solutions - TCHIO TCHINDA MARTIN GUILLAUME; Dr Dioba Sacko (Utilitas Mathematica, 2025)
It is imminent that the arrival of quantum computing is a real threat to data security in IaaS, in transit as well as at rest. To find cryptographic schemes capable of dealing with powerful quantum algorithms such as Shor and Grover, this article proposes an evaluative study of hybrid cryptographic solutions, which combines classical algorithms such as RSA2, ECC3, with post-quantum algorithms such as Kyber and Dilithium, capable of maintaining the same performance levels in an IaaS environment, and at the same time face the power of quantum systems. To do this, several metrics will be analyzed, including latency, CPU4 load, RAM5 saturation, and resistance to quantum attacks to have an objective idea of their possible adaptation (hybrid solutions) in the different IaaS environments of our main IaaS resource providers around the world, with a view to ensuring a transition to fully PQC solutions.